Viet Nam : Reform and Stabilization, 1986-1992 - Spitaller, Erich; Lipworth, Gabrielle (Washington, D.C. : International Monetary Fund, 1993)
Viet Nam has made substantial progress in the transition to a market economy and toward financial stability since economic reform began in 1986. Piecemeal measures were adopted at first, followed by the launching of a bold and comprehensive program of structural reform in March 1989. Complemented by policies designed to achieve financial stabilization, the program met early success. Its continuation, however, was put at risk by the withdrawal of external financing by the former Soviet Union and the breakdown of preferential arrangements with the CMEA area. Although economic performance weakened temporarily in the wake of these shocks, the Vietnamese intensified the adjustment process. Viet Nam has since resumed its progress toward financial stability and sustained growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet